Quality Characteristics and Sensory Evolution of Yogurt Supplemented with Soy Milk and Goji Berry Extract (Journal of Pharmaceutical Negative Results, 2023)
This study was conducted to investigating the possibility of producing functional yogurt from blends of toned and soy milk using goji berry extract. Different combinations were prepared with soy milk and goji berry extract. The addition of the soy milk and aqueous extract of goji berry by different concentration was significantly changed the organoleptic and physiochemical properties of yogurt. The functional yogurt (TS2G1) with 20% soy milk and 5% goji berry extract were recorded highest (7.32) overall acceptability on the bases sensory evaluation. Based on the present results the further studies can be proposed for production of functional yogurt with soy milk and goji berry extract, as potential natural antioxidant source.